The Effect of Shielding Gas Flow Rate on Fiber Laser Welding of Boron Steel - K. I., Yaakob; M., Ishak; Siti Rabiatull Aisha, Idris (2016)
During laser welding process, the ionized metal vapor from keyhole surrounding by molten metal mixes with the shielding gas and forms a plasma plume over the molten pool. The small amount of plasma plume is needed to react with molten pool by enhancing the absorption of laser energy thus increase the penetration. However, high amount of plasma will absorb the beam energy and this could decreases the penetration depth. The small wavelength of laser beam such as fiber laser, reported has less influence to plasma plume compared to bigger wavelength such as CO2 laser. However, even though using small wavelength laser, the laser beam with welding speed below 17mm/s had to go through the plasma plume over the molten pool. The suppression of plasma plume is highly influenced by shielding gas setup and flow rate. In this study, the effect of shielding gas flow rate (Argon) on CW and PW mode on low power fiber laser welding of Boron steel (22MnB5) was investigated. The observation of welding surface, width and depth were carried out. The width and depth pattern of CW and PW were slightly different. The range of 10-20L/min shows the widest width and 15L/min shows the deepest penetration for both welding mode.